PHILOSOPHY’S HUMANISTIC DYNAMISM - Christodoulou, Ioannis (European Scientific Journal, ESJ, 2014)
During the long humanistic intellectual history, philosophers used to be the forerunners of humanistic civilization. Nowadays, although remaining a famous discipline of Humanities, Philosophy seems not to be considered as the indubitable refuge of Humanism. In my opinion, the current academic politics does not coincide with the fulfilling of Philosophy’s alleged humanistic aspirations. On the one side, philosophers’ admirable academic achievements are not widely recognized. On the other side, academic philosophers themselves do not seem to be caring a lot about the public impact of their research. As a matter of fact, only a few academic philosophers made the cultural impact of Philosophy their constant academic concern. One of the most famous philosophers, who really made a subject out of their concern about the future of Philosophy, was Richard Rorty. Although I am not eager to accept Rorty’s pessimism regarding Philosophy’s role in expanding the territories of scientific knowledge, I am totally convinced that Rorty’s ideas concerning the cultural mission of Philosophy are well worth considering, provided that one has strong feelings about Philosophy’s place in human civilization. My own contribution rests on my analysis on the crisis of Philosophy’s strategic role in the leadership of Humanities. What I propose, is the reconsidering of the value of philosophical texts themselves, old and new ones. If Philosophy is to play a role in the rebirth of Humanities, philosophers may have to reconsider the value of the tradition of philosophical writing itself, instead of their obsession with ideas alone. We may have to re-establish the spontaneous productivity of philosophical expression, as the means of the re-entering of Philosophy in the path of humanistic excellence.